A Systematic Literature Review of Uses and Gratifications of Media During the COVID-19 Pandemic - Muhammad Nurhadi Tri Wibowo; Irwansyah Irwansyah (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2023)
Uses and gratification theory has five basic assumptions to answer how the media is used to meet audience needs. The COVID-19 pandemic required the public, especially the audience, to have distance difficulties when communicating. Communication media is an alternative to meet the satisfaction and needs of communication. This research synthesizes nine journal articles identified as the main data sources using a systematic literature review. The study results show that the five basic uses and gratification theory assumptions can be found in the service and satisfaction of media needs during the COVID-19 pandemic. Audiences use communication media during the COVID-19 pandemic with various goals, conditions, and influences. Communication media is also a means of conveying accurate information and is the main choice as a means of communication. It is hoped that this research can be used as an additional reference in research related to the use of the theory of use and gravity, as well as research related to the use of media during the Covid-19 pandemic, and can help agencies associated with the handling of Covid-19, media owners and media users as a whole general.